KERJA SAMA INDONESIA DENGAN AUSTRALIA DALAM BIDANG KEAMANAN MARITIM PADA TAHUN 2017-2019 - Nadya Putri Ramadhany; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research examines the repositioning of Indonesia and Australia’s maritime cooperation. Indonesia and Australia initiated their maritime cooperation in 2017 through the Joint Declaration on Maritime Cooperation, which was implemented with a plan of action in 2018. This cooperation was then incorporated into an extensive form of cooperation form through Indonesia-Australia Comprehensive Strategic Partnership in 2018, which was implemented with a plan of action in 2020. This research looks at the rationales behind the decision to rearrange the maritime cooperation into a more comprehensive agreement.This research uses descriptive explanative method, extracting sources from books, journals, official documents and official pages from the Indonesian Ministry of Foreign Affairs, the Australian Department of Defense, and the Australian Department of Foreign Affairs and Trade which are used to analyze the maritime cooperation between Indonesia and Australia. The perspective used in this research is neoliberalism that serves as the basis for international cooperation theory. It is said that states are looking for absolute gains in when they are cooperating with other states.This research indicates that the readjustment of a maritime cooperation between Indonesia and Australia has been influenced by the significance of Asia Pacific region in their foreign policies. Indonesia emphasizes its interest in the region under the World Maritime Axis (PMD) proclaimed during the Jokowi administration in 2014. Meanwhile, Australia outlines its Indo-Pacific Strategy (IPS) in the 2017 Australian Foreign Policy White Paper together with the 2016 Australian Defense White Paper. Keywords: International Cooperation, Maritime Security, World Maritime Axis, Indo-Pacific Strategy, Comprehensive Strategic Partnership Indonesia-Australia.